PLACE OF TICAGRELOR IN THE NEW RECOMMENDATIONS FOR THE MANAGEMENT OF PATIENTS WITH ACUTE CORONARY SYNDROME - A. D. Ehrlich (Атеротромбоз, 2015)
This article presents the main results of large clinical studies that explored the efficacy and safety of antiplatelet agent, P2Y12 inhibitor, ticagrelor. The PLATO, ATLANTIC and PAGASUS-TIMI-54 studies' results formed the basis for inclusion of ticagrelor in the clinical recommendations for the management of acute coronary syndrome (ACS). These guidelines designate ticagrelor as the main drug that should be added to acetylsalicylic acid as a component of dual antiplatelet therapy (DAT) in patients with ACS. The new 2015 recommendations for the management of patients with non-ST elevation acute coronary syndrome not only give preference to tikagrelor over clopido-grel, but also make it possible for some patients with a high risk of coronary complications and low risk of bleeding to extend DAT for longer than 12 months. In addition, the article presents data on some ACS registers held in Russia to estimate the frequency of tikagrelor administration.